2021
DOI: 10.1111/jtsb.12295
|View full text |Cite
|
Sign up to set email alerts
|

Why study turn‐taking sequences in interspecies interactions?

Abstract: The "turn-taking" system, a notion referring to the dynamics of verbal exchanges in face-to-face interaction, is often presented as the hallmark of human language (Levinson, 2016). However, recent works have investigated turn-taking mechanisms in several nonhuman taxa, thus referring to the moment-by-moment coordinated alternation of actions or vocalizations, for instance in primates or birds. These findings have been interpreted as evidence of elementary forms of sequence organization in the animal world, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
0
15
0
3
Order By: Relevance
“…We use this framework to review existing evidence and exemplify it by analysing examples of video-recorded interactions of chimpanzees, bonobos and humans. In doing so, we hope our research framework can be used as a template to produce systematic, comparative data on joint action in nonhuman animal species, and contribute towards stronger empirical foundations for the cross-species investigation of communicative behaviour [15][16][17]. With more comparative evidence on interactional structures across species, we may be able to trace evolutionary continuities in strategies for the resolution of communicative trouble, and to assess the extent to which repair may be part of a human-unique foundation on which language has evolved [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use this framework to review existing evidence and exemplify it by analysing examples of video-recorded interactions of chimpanzees, bonobos and humans. In doing so, we hope our research framework can be used as a template to produce systematic, comparative data on joint action in nonhuman animal species, and contribute towards stronger empirical foundations for the cross-species investigation of communicative behaviour [15][16][17]. With more comparative evidence on interactional structures across species, we may be able to trace evolutionary continuities in strategies for the resolution of communicative trouble, and to assess the extent to which repair may be part of a human-unique foundation on which language has evolved [8].…”
Section: Introductionmentioning
confidence: 99%
“…We see a productive methodological convergence between approaches rooted in conversation analysis [18,19,12] and primate interaction [3,15,20]; a possibility that has been hinted at sporadically [21][22][23] but only now, with the increasing availability of rich multimodal interactional data, is coming within reach. To make visible the convergence between disciplines, we start by defining and unpacking human concepts of repair (selfinitiated repair and other-initiated repair), to then translate them into species-agnostic phenomena that can be studied in non-linguistic species like nonhuman great apes.…”
Section: Introductionmentioning
confidence: 99%
“…This has been recognized among infants, prior to the acquisition of language: children learn the principles of turn-taking before learning to speak [30], and they discover very early on the consequentiality of a first action on the next [31,32]. Moreover, not only turn-taking [33][34][35], but also sequence organization has been identified among animals [36][37][38][39][40]. This article contributes to the latter line of research, by demonstrating how engaging in openings and greetings, baboons treat the expectations set up by the action initiating a sequence, and inspect the sequential slot in which a second action is expected and publicly orient to its possible absence.…”
Section: Background: the Sequence Organization Of Openingsmentioning
confidence: 99%
“…A large array of comparative research on non-human primates has now demonstrated that at least some of the basic building blocks of repair are present beyond humans (e.g. turn-taking, [10][11][12] and flexible signalling via repetition and elaboration, [10,11]). Such findings suggest a potential evolutionary continuum of repair, insofar as the sophisticated cognitive processes constituting it (i.e.…”
Section: Introductionmentioning
confidence: 99%